Outcomes following revision surgery performed for adverse reactions to metal debris in non-metal-on-metal hip arthroplasty patients: Analysis of 185 revisions from the National Joint Registry for England and Wales. Issue 7 (July 2017) - Matharu, G. S.; Judge, A.; Murray, D. W.; Pandit, H. G.
Abstract : Objectives: Few studies have assessed outcomes following non-metal-on-metal hip arthroplasty (non-MoMHA) revision surgery performed for adverse reactions to metal debris (ARMD). We assessed outcomes following non-MoMHA revision surgery performed for ARMD, and identified predictors of re-revision. Methods: We performed a retrospective observational study using data from the National Joint Registry for England and Wales. All non-MoMHAs undergoing revision surgery for ARMD between 2008 and 2014 were included (185 hips in 185 patients). Outcome measures following ARMD revision were intra-operative complications, mortality and re-revision surgery. Predictors of re-revision were identified using Cox regression. Results: Intra-operative complications occurred in 6.0% (n = 11) of the 185 cases. The cumulative four-year patient survival rate was 98.2% (95% CI 92.9 to 99.5). Re-revision surgery was performed in 13.5% (n = 25) of hips at a mean time of 1.2 years (0.1 to 3.1 years) following ARMD revision. Infection (32%; n = 8), dislocation/subluxation (24%; n = 6), and aseptic loosening (24%; n = 6) were the most common re-revision indications. The cumulative four-year implant survival rate was 83.8% (95% CI 76.7 to 88.9). Multivariable analysis identified three predictors of re-revision: multiple revision indications (hazard ratio (HR) = 2.78; 95% CI 1.03 to 7.49; p = 0.043); selective component revisions (HR = 5.76; 95% CI 1.28 to 25.9; p = 0.022); and ceramic-on-polyethylene revision bearings (HR = 3.08; 95% CI 1.01 to 9.36; p = 0.047). Conclusions: Non-MoMHAs revised for ARMD have a high short-term risk of re-revision, with important predictors of future re-revision including selective component revision, multiple revision indications, and ceramic-on-polyethylene revision bearings. Our findings may help counsel patients about the risks of ARMD revision, and guide reconstructive decisions. Future studies attempting to validate the predictors identified should also assess the effects of implant design (metallurgy and modularity), given that this was an important study limitation potentially influencing the reported prognostic factors. Cite this article: G. S. Matharu, A. Judge, D. W. Murray, H. G. Pandit. Outcomes following revision surgery performed for adverse reactions to metal debris in non-metal-on-metal hip arthroplasty patients: Analysis of 185 revisions from the National Joint Registry for England and Wales. Bone Joint Res 2017;6:405–413. DOI: 10.1302/2046-3758.67.BJR-2017-0017.R2.